Pengaruh Fraud Diamond Terhadap Kecenderungan Kecurangan Laporan Keuangan Yang Terdaftar di BEI Tahun 2019-2021 - Michi Natasa Wea; Wilhelmina Mitan; Siktania Maria Diliana (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the effect of fraud diamonds on the tendency for fraudulent financial reports in Manufacturing Companies in the Consumer Goods Industry Sub-Sector listed on the IDX in 2019-2021. This research was conducted using the associative causal method. The sample selection in this study used a purposive sampling method, with the sample criteria being the financial reports of 10 companies in the Consumer Goods Industry Sub-Sector Manufacturing Company registered on the IDX in 2019-2021. This research data was obtained from literature and documentation studies, data analysis techniques were obtained from IBM SPSS statistics version 26. Data analysis used in this research is, descriptive statistics, classical assumption tests using normality tests, autocorrelation tests, multicollinearity tests and heteroscedasticity tests, analysis multiple linear regression, hypothesis testing using partial test (t), simultaneous test (f) and coefficient of determination test (R2). The results of the research partially show that external pressure and ineffective supervision have proven to have a positive effect on financial report fraud. Meanwhile, the financial target variables, change of auditor, change of director were proven to have no positive effect on financial statement fraud. The variables pressure, opportunity, rationalization and ability simultaneously have a significant effect on financial statement fraud at a significant level of 5%. In this research, the fraud variable is explained by independent variables by 31.3%, the remaining 68.7% is explained by other external factors which are not in this study.